Association of Bipolar Disorder With Major Adverse Cardiovascular Events: A Population-Based Historical Cohort Study. Issue 1 (4th January 2022) - Foroughi, Moein; Medina Inojosa, Jose R.; Lopez-Jimenez, Francisco; Saeidifard, Farzane; Suarez, Laura; Stokin, Gorazd B.; Prieto, Miguel L.; Rocca, Walter A.; Frye, Mark A.; Morgan, Robert J.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: This study aimed to assess the association of bipolar disorder (BD) with risk of major adverse cardiac events (MACEs) after adjusting for established cardiovascular disease (CVD) risk factors. Methods: We conducted a population-based historical cohort study using the Rochester Epidemiology Project. Patients older than 30 years with a clinical encounter from 1998 to 2000 with no prior MACE, atrial fibrillation, or heart failure were followed up through March 1, 2016. BD diagnosis was validated by chart review. Cox proportional hazards regression models were adjusted for established CVD risk factors, alcohol use disorder, other substance use disorders (SUDs), and major depressive disorder (MDD). Results: The cohort included 288 individuals with BD (0.81%) and 35, 326 individuals without BD as the reference group (Ref). Median (interquartile range) follow-up was 16.5 (14.6–17.5) years. A total of 5636 MACE events occurred (BD, 59; Ref, 5577). Survival analysis showed an association between BD and MACE (median event-free-survival rates: BD, 0.80; Ref, 0.86; log-rank p = .018). Multivariate regression adjusting for age and sex also yielded an association between BD and MACE (hazard ratio [HR] = 1.93; 95% confidence interval [CI] = 1.43–2.52; p < .001). The association remained significant after further adjusting for smoking, diabetes mellitus, hypertension, high-density lipoprotein cholesterol, and body mass index (HR = 1.66; 95% CI = 1.17–2.28; p = .006), and for alcohol use disorder, SUD, and MDD (HR = 1.56; 95% CI = 1.09–2.14; p = .010). Conclusions: In this study, BD was associated with an increased risk of MACE, which persisted after adjusting for established CVD risk factors, SUDs, and MDD. These results suggest that BD is an independent risk factor for major clinical cardiac disease outcomes.